41 Beaumont hospital cardiology ANP led virtual clinic facilitates the safe discharge and appropriate follow- up of patients with range of low/intermediate risk acute cardiac conditions from the emergency department. (16th October 2019) - Stoneman, P; Adams, J; Colbert, F; Hussein, H; Foley, D; Sheahan, R; Gumbrielle, T; McAdam, BF; Kennedy, M; Mahon, P
Abstract : Introduction: Many patients who present to E/D with low or intermediate risk cardiac presentations can be safely managed with out-patient ambulatory diagnostics strategy. The lack of definitive outpatient pathways to safely manage these patients has a significant impact on admissions and length of stay adding to the current bed crisis and overcrowding of Emergency Department (E/D). A novel collaborative approach to this problem involved the implementation of a Cardiology ANP led Virtual Clinic outpatient ambulatory pathway which facilitates the referral of non ACS chest discomfort, rate controlled atrial fibrillation/flutter/pSVT, stable heart failure, HTN, incidental murmur, low risk collapse/syncope from the ED and provides patients with rapid access to a comprehensive range of outpatient cardiology diagnostics prior to referral to OPD when necessary. Aims/Objectives: To determine the benefit of an ANP-led Virtual Cardiology Clinic to the patient and the organisation. Methodology: Clinic referrals from January 2017 - December 2017 were audited. Data was collected prospectively as patients were referred to the service and those referred patients underwent case review (History/exam/Bloods/CXR/ECG) and when required, were contacted by phone. If indicated, appropriate diagnostics were requested, results reviewed then referred on to consultant clinic only if indicated. Results/Discussion: 894 patients were referred. 9 patients (1%) recalled to ED. A significant 254 (28%) were deemed not to require diagnostics and discharged to GP. 732 diagnostic tests were performed on 640 patients including 201 functional stress tests (13 abnormal), 38 coronary day case angiograms (10 of which required PCI), 292 Holters, 97 ECHOs (13 minor abnormalities), 68 CTCA, 12 DCCV, 73 24 hour BP. 186 patients were subsequently referred to cardiology OPD. There were 2, 145 acute beds saved (based on 2.4 LOS) with estimated savings of €2, 4000, 000. Conclusion: The Cardiology ANP led Virtual Clinic is a safe and efficient pathway that pre – filters ED referrals resulting in reduced waiting time in the Emergency Department, unnecessary travel back to the hospital (further reducing travel time, costs, waiting times), unnecessary referral to cardiology outpatients (reducing outpatient department overcrowding and waiting times). In a 12-month period, this initiative has saved Beaumont Hospital an estimated 2.4 million Euro and 2, 145 acute hospital bed days. Implications: Cardiology ANP led Virtual Clinics have the potential for a significant impact around the country with regards to the appropriate and efficient management of acute cardiology presentations to E/D with early access to outpatient cardiology ambulatory diagnostics and appropriate referral to outpatient consultant cardiology clinics or d/c to GP.